Study on spray nozzle of diesel engine - Nur Syafiqah, Mohd Nawawi (2011)
This project presents the study about development and analysing existing technology of designation in an indirect injection diesel injector of a diesel engine. The objective of this project is to design the new spray nozzle by using calculated data of the chosen aspect, fabricate the new nozzle and the new nozzle injector can be used and able to function. The scopes of this research are reviewing the important devices that related to the experiment, studying the properties of spray nozzle in fuel injector, fabricate the new fuel injector nozzle using the suitable process after design it using Solidworks and testing the performance and spray pattern of new nozzle injector using the nozzle tester. Experiment was done by supplying pressure at 104 bar and 124 bar by using nozzle tester. The image of spray from nozzle injector was captured and the result based on criteria shows that the new nozzle injector can function properly. The new nozzle injector occupies lesser space compared from previous nozzle injectors that are too bulky and large. The new nozzle injector offers improvements over the previous nozzle injector in installation.